(untitled) (Al-Mansour Journal, 2022)
Robotic path-planning is a major problem in the robotic world, and one of the most used algorithms in this area is the A* algorithm. This paper presents a modified A* Algorithm that can work in a Three-Dimensional (3D) sphere environment and allows the moving of robot to reach its goal while avoiding obstacles on its path, solve local minima problems, safety rim and accurate convergence. The F(n)* evaluation function has been used in the proposed modified A*. Simulation results showed that the proposed modified A* guarantee to find near optimal, safe path from the start position to goal point in 3D static sphere environment with acceptable execution time.